2011
DOI: 10.1007/s11910-011-0241-8
|View full text |Cite
|
Sign up to set email alerts
|

Tools and Early Management of Language and Swallowing Disorders in Acute Stroke Patients

Abstract: The role of the stroke units in improving morbidity, mortality, and recovery from stroke is clearly demonstrated. However, acute management of language disorders in these specialized units remains controversial, and management of swallowing disorders is usually nonstandardized. The recent validation of a scale for rapid screening of language disorders (LAST [Language Screening Test]) in acute stroke patients should allow optimization of their detection and early management. Swallowing disorders should be scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Consequently, separate rapid screening tools for swallowing and communication are highly advisable. To ensure monitoring of suspected rapid recovery or deterioration, repeat testing with validated rapid screening tools is essential [42]. …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, separate rapid screening tools for swallowing and communication are highly advisable. To ensure monitoring of suspected rapid recovery or deterioration, repeat testing with validated rapid screening tools is essential [42]. …”
Section: Discussionmentioning
confidence: 99%
“…Failure of normal pharyngeal muscle function can also manifest as dysphagia (swallowing impairment), which is common in the immediate days following acute stroke (Brogan, Langdon, Brookes, Budgeon, & Blacker, 2014). Indeed, the occurrence of dysphagia in acute stroke is reported to be as high as 50% (Flamand-Roze, Cauquil-Michon, & Denier, 2012). Its presence is often accompanied by poor clinical outcomes, including longer hospitalization and higher mortality (Martino, Beaton, & Diamant, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, these models have shown low to moderate performance. Dysphagia, a symptom frequently observed in stroke patients, impacts an estimated 38.5 to 50% of individuals who have experienced a stroke [ 57 , 58 ]. Previous research has indicated that dysphagia serves as an independent risk factor for stroke patients with OSA [ 59 ].…”
Section: Discussionmentioning
confidence: 99%